Critical Analysis of Right of Rescission in Unilateral Acts - sam mohammadi; Hiva abdolkarimi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2017)
Right of rescission is one of the main topics of contract law in Islamicjurisprudence as well as in Iranian Law. Jurists and lawyers havedevoted part of their books to this topic. The issue discussed in this areais the scope of right of rescission, called " necessary contracts" by juristsand legal scholars. In other words, legal acts lacking the description"contract" and "necessary" are exempted from being subject to the rightof rescission. Although supporters of this opinion have put forwardreasons to justify it and it is seemingly logical, a careful look at reasonsgiven, criticisms , principles of right of rescission, rules of contract lawand principles of interpretation proves the opposite view and not thefamous one. This article examines famous and opposite opinions byconducting a critical analysis.